SHOECITO PATCH: POTENSI LIMBAH AMPAS KOPI DAN KULIT JERUK SEBAGAI ECO-FRIENDLY SHOE DEODORIZING PATCH UNTUK MENGATASI BAU SEPATU - Warsito, Ahmad Nur Aziz Ronggo; Islakhiyah , Dina Dalilatul; Nafisah , Faridatun; Putri , Salma Aulia; Ismail , Hudan; Mufiidah , Nurhidayatul; Hilma , Rista Aulia Warosyatul; Farahita , Senja Dewi (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
The use of natural materials in personal care products is gaining attention as awareness of environmental issues increases. In efforts to reduce the use of synthetic chemicals in shoe care products, coffee grounds waste and citrus peel have emerged as promising eco-friendly solutions. This article discusses the potential utilization of these natural materials as raw ingredients for the production of an eco-friendly shoe deodorizing patch. Coffee grounds, rich in antibacterial compounds and odor-absorbing capabilities, are combined with essential oils from citrus peel that provide a fresh aroma. By integrating coffee grounds and citrus peel, this deodorizing patch not only effectively addresses unpleasant odors in shoes but also supports sustainability principles. In addition to offering practical benefits, the use of natural materials helps reduce waste and supports the zero-waste movement. Through the utilization of commonly available organic waste, this product offers a healthy and sustainable alternative to commercial shoe deodorizers while promoting awareness of the importance of environmentally-based solutions.